Nuclear Power and Energy Security - Apikyan, Samuel A.; Diamond, David J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
World energy consumption has grown dramatically over the past few decades. This growth in energy demand will be driven by large increases in both economic growth and world population coupled with rising living standards in rapidly growing countries. The last years, we routinely hear about a "renaissance" of nuclear energy. The recognition that nuclear power is vital to global energy security in the 21st century has been growing for some time. "The more we look to the future, the more we can expect countries to be considering the potential benefits that expanding nuclear power has to offer for the global environment and for economic growth," IAEA Director General Mohamed ElBaradei said in advance of a gathering of 500 nuclear power experts assembled in Moscow for the "International Conference on Fifty Years of Nuclear Power - the Next Fifty Years". But such a renaissance is not a single-valued and sure thing. Legitimate four unresolved questions remain about high relative costs; perceived adverse safety, environmental, and health effects; potential security risks stemming from proliferation; and unresolved challenges in long-term management of nuclear wastes. Failure to answer these questions adequately could imperil the nuclear revival so many have proclaimed is night. This proceeding examines the status and future of nuclear power because of a belief that this technology is an important option for the regional and the world countries to meet the future energy needs without emitting carbon dioxide and other atmospheric pollutants. The objectives, addressed to government, industry, and academic leaders, discusses the interrelated technical, economic, environmental and political challenges facing a significant increase in the global nuclear power utilization over the next half century and what might be done to overcome those challenges.
Developing The Necessary Infrastructure -- Iaea Activities In Support Of Countries Considering Embarking On Nuclear Power Programme -- Creating a National Nuclear Regulatory Authority -- Building Safeguards Infrastructure -- Regulatory Challenges Related to The Licensing of a New Nuclear Power Plant -- Infrastructure Development Through Civil Nuclear Cooperation -- Nuclear Safety Infrastructure -- Upgrading Nuclear Regulatory Infrastructure in Armenia -- Seven Principles of Highly Effective Nuclear Energy Programs -- The Case for Nuclear Energy -- Nuclear Safety and Energy Security -- Nuclear Energy and Social Impact -- The Role of Nuclear Power in the Reduction of Greenhouse Gas Emissions -- Nuclear Energy & Energy Security -- Overview of the Electricity Market of Estonia and the Plausibility of Nuclear Energy Production -- The Role of Small And Medium Reactors in the Energy Security of a Country, Iris Example -- Applicable Technology -- Status Report on the Safety of Operating US Nuclear Power Plants (why Experts Believe that Today'S Operating Nuclear Power Reactors are Much Safer than they Were 20 Years Ago) -- Nato-Astec-Matrix$1 (BResearch Environment, Information Sharing and Mc&A -- Establishing Control Over Nuclear Materials and Radiation Sources in Georgia -- Nuclear Energy in Armenia History, Problems, Possibilities and Outlook -- Development of Nuclear Energy in Armenia -- Some Neutron Absorbing Elements and Devices For Fast Nuclear Reactors Regulation Systems -- Development of Design of a Radioisotope Switchable Neutron Source and New Portable Detector of Smuggling -- New Designs of Medium Power Vver Reactor Plants -- National Assessment Study in Armenia Using Innovative Nuclear Reactors and Fuel Cycles Methodology for an Innovative Nuclear Systems in a Country with Small Grid -- Candle Reactor: an Option for Simple, Safe, High Nuclear Proliferation Resistant, Small Waste and Efficient Fuel use Reactor -- Emissions of the Corrosion Radionuclides in an Atmosphere -- Iaea Support For Operating Nuclear Reactors -- The Solid Coolant and Prospects of its use in Innovative Reactors -- Innovation Projects of Atomic Energy Institute of National Nuclear Center Rk in the Area of Peaceful use of Atomic Energy -- Innovative Designs of Nuclear Reactors -- Development of Devices For Handling with Bn-350 Radioactive Waste -- Institutional Support to the Nuclear Power Based on Transportable Installations -- International Cooperation and Security in the Field of Nuclear Energy in Armenia -- Applied Model of Through-Wall Crack of Coolant Vessels of Vver-Type Reactors.s
Keywords: Engineering; Particle acceleration; Nuclear fusion; System safety; Nuclear engineering; Environmental protection; Engineering; Nuclear Engineering; Effects of Radiation/Radiation Protection; Particle Acceleration and Detection, Beam Physics; Quality Control, Reliability, Safety and Risk; Nuclear Fusion